The kidney in aging - Ferder, Leon (2007)
Aging is a slow, inflammatory biological process that affects many organs of which the kidney is one of the main targets. Aging is associated with a decline in renal function coincident with a progressive loss of nephrons, with glomerular and tubulointerstitial scarring. These changes begin in the fourth decade of life and accelerate between the 5th and 6th decade, resulting in alterations in glomerular and tubular function, systemic hemodynamics and body homeostasis. While aging-related changes begin in mid-life, most of the discussion will revolve around the management of the older population, defined as > 65 years of age. It is important to realize that aging-associated renal disease may not be an inevitable consequence of life. Some subjects do not show age-related decline in GFR, and in some populations hypertension does not increase with aging, the latter occurring primarily in non-Westernized groups habitually on low sodium diets. This has led some to hypothesize that aging-associated renal disease may be an active process that is potentially preventable.